2022
DOI: 10.1002/saj2.20428
|View full text |Cite
|
Sign up to set email alerts
|

Selecting soil hydraulic properties as indicators of soil health: Measurement response to management and site characteristics

Abstract: Farmers, scientists, and other soil health stakeholders require interpretable indicators of soil hydraulic function. Determining which indicators to use has been difficult because of measurement disconformity, spatial and temporal variability, recently established treatments, and the effect of site characteristics on management practice differences. The North American Project to Evaluate Soil Health Measurements includes 124 sites uniformly sampled across a range of soil health management practices in North Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…In general, these studies found the largest increases in soil C stocks near the surface. While this manuscript has focused on the increase of SOC concentrations in response to management, bulk density did show a significant negative response to decreased tillage, organic nutrients, and residue retention in NAPESHM dataset (Bagnall et al, 2022). Because the change in SOC concentration was so much larger than the change in bulk density in the NAPESHM dataset, the effect size of the meta-analysis of C stocks would differ by less than 1%.…”
Section: Response To Managementmentioning
confidence: 79%
“…In general, these studies found the largest increases in soil C stocks near the surface. While this manuscript has focused on the increase of SOC concentrations in response to management, bulk density did show a significant negative response to decreased tillage, organic nutrients, and residue retention in NAPESHM dataset (Bagnall et al, 2022). Because the change in SOC concentration was so much larger than the change in bulk density in the NAPESHM dataset, the effect size of the meta-analysis of C stocks would differ by less than 1%.…”
Section: Response To Managementmentioning
confidence: 79%
“…2), and management systems (Tables 1-8), each is unique and arguably very different from the next. NAPESHM results utilized these existing experiments with a wider network of sites to compare the response of soil measurements to similar soil health treatments across sites (e.g., Liptzin et al 2022;Rieke et al 2022;Bagnall et al 2022). These results highlight the importance of a large and wide network to discern a signal from the noise of highly variable site conditions.…”
Section: Discussionmentioning
confidence: 95%
“…1). Results from this project are now being published in aggregate from sites spanning from Mexico to Canada (Bagnall et al 2022;Liptzin et al 2022;Rieke et al 2022). We recognize there are other LTRs in Canada, but our objectives here are to use the NAPESHM sites in Canada to illustrate how LTRs are important to our national interest through (i) highlighting the breadth and depth of knowledge gained previously from the sites, (ii) illustrating the diversity of soils sampled and to provide a foundational background for future analysis, and (iii) discussing how these and other LTRs can continue to address future questions of stakeholders including governments, land managers, and society.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, bulk density values at both depths were lower than 1.55 g cm −3 , which is the bulk density considered to be root-restrictive for silt loam soils (Kaufmann et al, 2010). Nevertheless, lowered bulk densities are an indication of higher organic matter content, greater porosity, and improved soil hydraulic function (Kaufmann et al, 2010;Bagnal et al, 2022). The lower bulk density after 2 years of perennial forage, regardless of tillage, thus suggested that soils had better structure in support of root growth.…”
Section: Bulk Density and Calculation Of Total Organic C By Volumementioning
confidence: 94%